2020
DOI: 10.3390/nu12072047
|View full text |Cite
|
Sign up to set email alerts
|

Living in Rural and Urban Areas of New Caledonia: Impact on Food Consumption, Sleep Duration and Anthropometric Parameters Among Melanesian Adolescents

Abstract: Background: Food consumption, sleep duration and overweight were assessed in rural and urban Melanesian adolescents. Methods: A cross-sectional survey of 312 rural and 104 urban adolescents (11–16 years old) was conducted. Food intakes were assessed by a 26-item food frequency questionnaire and then categorised into the number of serves from each of the three recommended Pacific food groups (energy foods, protective foods, bodybuilding foods), with two additional categories for foods and drinks to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…In rural areas, high scores for traditional ONENA Fruits and vegetables pattern and low scores for the Dairies and breakfast pattern were observed. These trends can be partly explained by the availability and affordability of these products [56] , [71] . Fruits and vegetables are commonly cultivated in rural areas by traditional Melanesian family farms or bigger European farms and thus are widely available and affordable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rural areas, high scores for traditional ONENA Fruits and vegetables pattern and low scores for the Dairies and breakfast pattern were observed. These trends can be partly explained by the availability and affordability of these products [56] , [71] . Fruits and vegetables are commonly cultivated in rural areas by traditional Melanesian family farms or bigger European farms and thus are widely available and affordable.…”
Section: Discussionmentioning
confidence: 99%
“…The short questions on this FFQ are able to discriminate between different categories of food intake and provide information on relative intakes [54] . Moreover, this FFQ has been validated in a pluri-ethnic population composed with non-indigenous Australians (with European background) and Torres Strait Islanders (with a Melanesian background), and it was previously used in New Caledonia [56] . Minor modifications were made by the research team to include foods identified as important in the Melanesian diet.…”
Section: Methodsmentioning
confidence: 99%
“…High unhealthy food consumption with 27% of daily food intake was recently observed in Melanesian adolescents from New Caledonia. These dietary changes might explain the high percentage of overweight and obesity (38.1% for rural and 31.7% for urban adolescents) observed in this study, therefore, further comprehensive investigation of dietary intakes is needed [ 16 ]. In the future, the food and nutrient data within this database will be validated, in the context of the iRecall.24 app against 24-h recalls in children and adults in New Caledonia.…”
Section: Discussionmentioning
confidence: 99%
“…In Pacific communities, overweight and NCD progression have been accelerated by transitioning food environments facilitated by globalization and trade [ 10 , 11 , 12 , 13 , 14 ] combined with a decline in local agricultural and fishery practices [ 15 ]. Consequently, traditional nutrient-dense plant-based diets, particularly starchy tuber staples [ 16 ], have been replaced with imported energy-dense nutrient-poor processed foods and convenience fast foods high in saturated fat, added sugar, and/or added salt [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation